EFFORTS TO TEACHER GUIDANCE AND COUNSELLING IN UNDERSTANDING THE MORAL OF STUDENT - Erlina Harahap (Universitas Muhammadiyah Tapanuli Selatan, 2016)
This study is based on problems that (1) Teachers have not been up to implement the service of moral guidance in understanding the student information. (2) Students are difficult to interact with their peers. (3) students against teachers. (4) Students speak harshly against the teacher. (5) Students are merely talking to the teacher. (6) Students who do not pay attention with less he spoke. The objectives to be achieved is to know teacher effort in understanding the moral Counseling students at SMAN 3 Padangsidimpuan TA. 2014-2015 located at Jln. Pioneer Independence No. 56 Tel. (0634) 22435 Padangsidimpuan. Guidance and Counseling Teacher class X, XI and XII is a research informants. The method used in this study is a kind of qualitative research methods were used to examine the condition of natural objects, where researchers as a key instrument. Data was collected by triangulation (combined) that observation (observation), interviews (interviews), the questionnaire (questionnaire), documentation and fourth combined. Based on the research efforts of teachers in guidance and counseling students' moral understanding that the Principal has little understanding of guidance and counseling so that the Principal wants to have extensive knowledge and the manner in which teachers BK in providing information services to students. Based on interviews with informants writer, teacher BK ask directly to students who do not know about the moral understanding and provide guidance to students who do not know about the moral understanding. The conclusion of this study is, Principal of the manner BK teachers in providing information services to the student's homeroom teacher by teacher BK cooperate in moral understanding of students. Teachers BK perform other tasks in the field of guidance and counseling as well as the exchange of information and discussion for quality improvement. Teachers BK evaluate all activities each time, which can be done every 1 month